ChemInform Abstract: KIO3‐Catalyzed Aerobic Cross‐Coupling Reactions of Enaminones and Thiophenols: Synthesis of Polyfunctionalized Alkenes by Metal‐Free C—H Sulfenylation. Issue 25 (June 2016) - Wan, Jie‐Ping; Zhong, Shanshan; Xie, Lili; Cao, Xiaoji; Liu, Yunyun; Wei, Li
Abstract: A new catalytic method for the α‐sulfenylation of enaminones and related enamines under environmentally benign conditions using ethyl lactate as bio‐based green solvent is developed.